POLA KOMUNIKASI PEREMPUAN DOUBLE BURDEN DALAM MEMBENTUK PERILAKU REMAJA DI KECAMATAN SELESAI KABUPATEN LANGKAT - Asrie Arianty; Nursapia Harahap (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Women who hold two roles at once, namely working while taking care of the household, need good time management to balance work affairs and build quality interactions with other family members. This research was conducted to determine how women's communication patterns with double burdens shape adolescent behavior. A descriptive qualitative research method with a phenomenological approach was used to understand the problem under study. The informants in this study were working mothers who had teenage children and lived in Selesai Subdistrict, Langkat Regency. The study found that some women with a double burden struggle to communicate with children. Regarding the application of communication patterns, it was found that mothers do not peg on one communication pattern only but use several communication patterns tailored to each purpose and benefit but tend to lead to one of the dominant communication patterns. It can be concluded that the correct communication patterns mothers apply can shape positive adolescent behavior.